The dragon's promise - Lim, Elizabeth (Lim, Elizabeth. Six crimson cranes duology, 2022)
"Princess Shiori made a deathbed promise to return the dragon's pearl to its rightful owner, but keeping that promise is more dangerous than she ever imagined. She must journey to the kingdom of dragons, navigate political intrigue among humans and dragons alike, fend off thieves who covet the pearl for themselves and will go to any lengths to get it, all while cultivating the appearance of a perfect princess to dissuade those who would see her burned at the stake for the magic that runs in her blood"--